EPIZOOTOLOGY OF ORIENTOBILGARCIOSIS OF SHEEP IN THE ARALSEEBUCHT (Intent Research Scientific Journal, 2023)
In recent years, the decrease in the annual volume of water in the Amu Darya and the sharp drop in the level of the Aral Sea caused by the impact of anthropogenic factors have led to intensive study of the climate and natural biogeocenoses of the Republic of Karakalpakstan. Such an ecological crisis primarily negatively affects the areas adjacent to the drying up Aral Sea. This process also has an impact on the epizootology of the causative agents of Trematodoses, common among farm animals, which have been causing great economic damage to animal husbandry for many years